The A to Z of journalism - Eaman, Ross (IG library, 2009)
Journalism is the discipline of gathering, writing, and reporting news, and it includes the process of editing and presenting news articles. Journalism applies to various media, including but not limited tonewspapers, magazines, radio, television, and the internet.